2010
DOI: 10.3390/en3121831
|View full text |Cite
|
Sign up to set email alerts
|

A New Hybrid Algorithm Using Thermodynamic and Backward Ray-Tracing Approaches for Modeling Luminescent Solar Concentrators

Abstract: A Luminescent Solar Concentrator (LSC) is a transparent plate containing luminescent material with photovoltaic (PV) cells attached to its edges. Sunlight entering the plate is absorbed by the luminescent material, which in turn emits light. The emitted light propagates through the plate and arrives at the PV cells through total internal reflection. The ratio of the area of the relatively cheap polymer plate to that of the expensive PV cells is increased, and the cost per unit of solar electricity can be reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…There are a number of reports of Cd-based nano-TP structures [164]. Unfortunately, as with other Cd based structures, the presence of highly toxic heavy metals greatly impedes the practical application of these nanomaterials, so obtaining its Cu-based counterparts is imperative.…”
Section: Synthesis Of Cu-based Multicomponent Heterostructuresmentioning
confidence: 99%
“…There are a number of reports of Cd-based nano-TP structures [164]. Unfortunately, as with other Cd based structures, the presence of highly toxic heavy metals greatly impedes the practical application of these nanomaterials, so obtaining its Cu-based counterparts is imperative.…”
Section: Synthesis Of Cu-based Multicomponent Heterostructuresmentioning
confidence: 99%
“…Part of the light striking the internal surface at very steep angles manages to escape the structure through escape cone of total internal reflection. Source: [46].…”
Section:  Mo Nps As Charge Transporting Layersmentioning
confidence: 99%
“…An important group of MOs possesses these properties, the most popular studied materials and their dopants are gathered in Table 2. Source: Authors', based on [46].…”
Section:  Mo Nps As Charge Transporting Layersmentioning
confidence: 99%
“…When coupled with gallium arsenide (GaAS) solar cells, their LSC design achieved an electrical conversion efficiency of 7.1%. Lo et al [47] created a new algorithm to evaluate the performance of an LSC and concluded that their new method is "a fast, powerful and cost-effective tool" to design any LSC. Pei et al [48] showed that the optical efficiency of a dielectric CPC can be improved by introducing a mirror coating on the sides of the concentrator, as high as 13.5%.…”
Section: Advantages Disadvantagesmentioning
confidence: 99%